Baseline bone marrow ADC value of diffusion-weighted MRI: a potential independent predictor for progression and death in patients with newly diagnosed multiple myeloma - Zhang, Lu; Wang, Qin; Wu, Xia; Zhao, Ailin; Feng, Jun; Zhang, Haibo; Cao, Xinxin; Li, Shuo; Cai, Huacong; Sun, Zhaoyong; Duan, Minghui; Zhu, Tienan; et al. (European radiology, 2021)
Objectives To illuminate the prognostic value of ADC (apparent diffusion coefficient), an important quantitative parameter of diffusion-weighted MRI, for multiple myeloma (MM). Methods A prospective single-center study which enrolled 114 consecutive newly diagnosed MM patients with baseline whole-body diffusion-weighted MRI (WB DW-MRI) results was conducted. Baseline clinical and MRI parameters were analyzed with univariate and multivariate approaches to identify independent risk factors for progression-free survival (PFS) and overall survival (OS). Results Five different DW-MRI patterns were seen, and the mean ADC value of the representative background bone marrow was 0.4662 ± 0.1939 × 10 −3 mm 2 /s. After a mean follow-up of 50.2 months (range, 15.7–75.8 months), twenty-four patients died and seven were lost to follow-up. The mean ADC value of the representative background bone marrow was showed to be an independent risk factor for both PFS (HR 4.664; 95% confidence interval (CI) 1.138–19.121; p = 0.032) and OS (HR 14.130; 95% CI 1.544–129.299; p = 0.019). Normal/salt-and-pepper pattern on DW-MRI was associated with PFS using univariate analysis ( p = 0.035) but lost the significance with multivariate Cox regression. Conclusions Mean ADC value of the representative background bone marrow predicts both PFS and OS which suggests the role of baseline DW-MRI for risk stratification in newly diagnosed MM patients. Key Points • Whole-body diffusion-weighted MRI (WB DW-MRI) might be helpful to improve the current risk stratification systems for newly diagnosed multiple myeloma (MM). • Morphological parameters as MRI pattern and focal lesion–associated parameters have been reported to be related to survival. However, important functional parameters such as apparent diffusion coefficient (ADC) values were not incorporated into the current risk stratification model. • This study is one of the first endeavors to delineate the correlation of baseline ADC values and survival in MM patients. It is revealed that the mean ADC value of the representative background bone marrow (L3-S1 and iliac bone) was an independent risk factor for both PFS and OS.